Physical activity epidemiology. - Dishman, Rod K., ....-; Heath, Gregory W., ....-; Lee, I-Min, ....- (Champaign (Ill.) : Human kinetics, 2013)
Physical Activity Epidemiology, Second Edition, provides a comprehensive discussion of population-level studies showing the influence of physical activity on disease. The text summarizes the available knowledge, details the methods used to obtain it, and considers its implications for public health.
Keywords: Lichamelijke inspanning; Sport en gezondheid; Sportgeneeskunde